Designing an Energy Literacy Curriculum Model with a Climate Change Approach in the Iranian Elementary Education System - Shakeri Seyedabadi, Elham; Rasouli, Seyedeh Esmat; Salimi, Ladan (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to design and evaluate an energy literacy curriculum model with a climate change approach tailored for the Iranian elementary education system. Methodology: The study utilized a qualitative research design, employing semi-structured interviews with 17 participants, including educators, curriculum specialists, and environmental education experts. Data were collected until theoretical saturation was reached and were analyzed using thematic analysis. The curriculum model was developed based on insights from the data and integrated hands-on activities, digital tools, and project-based learning. Pre- and post-intervention assessments were conducted to evaluate the curriculum's effectiveness in improving students' energy literacy and climate change awareness. Findings: The findings revealed significant improvements in students' energy literacy, particularly in understanding energy conservation, renewable energy sources, and the environmental impacts of energy use. The curriculum also successfully enhanced students' awareness of climate change and its connection to energy consumption. Key factors contributing to these outcomes included the use of project-based learning, interactive digital tools, and community-based projects, which collectively fostered deeper comprehension and application of energy concepts in real-world settings. Conclusion: The study demonstrates the effectiveness of an integrated energy literacy and climate change curriculum in improving elementary students' knowledge and attitudes. The findings suggest that project-based learning and digital tools are particularly effective in enhancing energy literacy. Despite some limitations, such as the study's limited geographic scope and potential teacher bias, the curriculum model offers a promising approach for promoting energy literacy and environmental stewardship among young students.